2023
DOI: 10.1080/25726838.2023.2166725
|View full text |Cite
|
Sign up to set email alerts
|

Compositional characteristics of mineralised and unmineralised gneisses and schist around the Abansuoso area, southwestern Ghana

Abstract: Gold-bearing granitoid deposits have recently been discovered in the Birimian of Ghana but their mode of formation and ore genesis remain enigmatic. This study presents petrographic, and geochemical characteristics of mineralised and unmineralised (gold grade >0.05 and <0.05 g/t respectively) granitoids (now gneisses) and schists (metasedimentary) to evaluate their petrogenesis/provenance, and relationship to gold mineralisation in the Abansuoso area. The unmineralised rocks comprise biotite-and hornblende-bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…It was observed that, regions within the metavolcanic and the volcaniclastic sediment dominated terrane, with intense lineation (due to the existence of fracture and shear zones along the north-central portion of the area) were delineated to be of moderate to high potential. This corroborates with literature as gold occurrence in Abansuoso Area is mostly observed along strongly sheared zones [ 3 ]. The MPM developed was further discretised into three classes using the natural breaking classification method into low, moderate and high prospectivity classes as shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…It was observed that, regions within the metavolcanic and the volcaniclastic sediment dominated terrane, with intense lineation (due to the existence of fracture and shear zones along the north-central portion of the area) were delineated to be of moderate to high potential. This corroborates with literature as gold occurrence in Abansuoso Area is mostly observed along strongly sheared zones [ 3 ]. The MPM developed was further discretised into three classes using the natural breaking classification method into low, moderate and high prospectivity classes as shown in Fig.…”
Section: Resultssupporting
confidence: 92%
“…The mineral influencing factors derived from the radiometric data generally characterise the radioelement (K, eTh and eU) concentration distribution over a region of interest [ 8 ]. The radiometric ratio maps (K/eTh, eU/eTh) particularly are undoubtedly significant in outlining mineralised hydrothermal zones as well as alteration zones that are relevant towards gold mineralisation occurrence within the Abansuoso Area and its related geological terranes [ 3 , 12 ]. Thus, four radiometric-sourced layers comprising K ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations